ANALISIS PERILAKU KONSUMEN PEREMPUAN TERHADAP KESEHATAN REPRODUKSI DAN PERILAKU PENGGUNAAN PEMBALUT - Julina Julina (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2012)
This research try to discover women consumer behavior towards their reproductive health and the use of pads. It was found that most respondent used magazines, newspapers, or newspapers as sources of information to acquire knowledge about reproductive health. Respondents spent special time to increase knowledge about reproductive health of women and prioritize read articles about women's reproductive health. Pads is one of product that is familiar with the women reproductive health, but women in this study had no certainty about its safety for use and whether the pads can cause cancer. Additionally, more than half of respondents would consider using the traditional way with a washable cloth pads if the current pads is proven can cause cervical cancer. Price of the pads is a factor that affects their purchase behavior and although they have a favorite brand, they are not particularly loyal to the brand if it is not available when needed.